Management of Septic Arthritis of the Temporomandibular Joint in Dogs - Arzi, Boaz; Vapniarsky, Natalia; Fulton, Amy; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2021)
Septic arthritis of the temporomandibular joint (TMJ) in dogs and other mammals is a rare condition. It is typically associated with notable pain, swelling, and difficulty in opening the mouth. Unlike degenerative TMJ disease, septic arthritis requires urgent intervention. The etiology of the condition may include penetrating trauma, an extension of local infection, such as otitis media, or the hematogenous spread of a pathogen. However, the precise cause may not always be identified. Diagnostic imaging with Computed Tomography (CT), cone-beam CT (CBCT), and/or Magnetic Resonance Imaging (MRI) are helpful for honing the definitive diagnosis and formulating a treatment plan. Subsequently, exploratory surgery may be required to obtain samples for culture and sensitivity and histology and to lavage the joint. In this “methods” article, we provide a detailed description of our approach to diagnosis and management of septic TMJ arthritis in four dogs.